The Effectiveness of Role Play on Changes Attitudes and Food Safety Practised Among School Aged Children - Lita Heni Kusumawardani; Aprilia Kartikasari; Koernia Nanda Pratama (Alta Dharma Publisher, 2021)
Health problems due to unsafe food in Indonesia often occur, especially amongst school-aged children. School-aged children need to give health education related to food safety to prevent food poisoning. This study aimed to determine the effect of role-playing on improving attitudes and practices regarding food safety amongst elementary school children in Purwokerto City, Banyumas Regency. The research method used a quasi-experimental design with a pre-post test using a control group. The total sample of the study was 102 school-aged children aged 6-12 years. The intervention group was treated in the form of a group process with the implementation of a role play for four weeks, carried out four times a month, and lasted for 40 minutes per session. The analysis of data performed using the paired t-test and independent t-test. This research showed that the health education method with a role-play could significantly improve attitudes and skills regarding food safety among school-aged children, significantly p <0.05. it can use the role-play method to improve the food safety behavior of school-aged children. The role-play method should be an effective and interactive health education intervention for elementary school-aged children